SIX THESES ABOUT MEMORY AND HEGEMONY, OR THE POLICY RETURN - Fernando Rosas (Germinal : Marxismo e Educação em Debate, 2009)
This text is about the memory as a stage for the classes struggles nowadays. In six theses is developed that: 1. the remembered or not remembered from the human practices from the 20th century is prepared in a hidden discussion, but that already causes noise; 2. that the discussion on the ownership for the memory is a part of the struggle for power; 3. that the memory isn’t worth by itself, but for the ownership and its use in the struggle for hegemony; 4. that the historiographical speech is not neutral; 5. that the neoliberal ideology run by media that reinforces a present that prevents the critical culture, concepts and values from a potential subversive, with obvious consequences on the exploitation of the labor, in the reformist political action, in the rehabilitation, in quiet, from the dictatorship policy practices, from salazarism, from colonialism; 6. that the resistance to the deletion of the memory is a task of the social movements. Finally, that the paths of the memory are the backbone of the identity of those who come from far in the political struggle. That this awareness of itself is the fulcrum of the entire emancipatory fighting. Because of this, we should have memory.